Characteristics of estrogenic/antiestrogenic activities during the anoxic/aerobic biotreatment process of simulated textile dyeing wastewater. Issue 30 (8th March 2016) - Liu, Na; Xie, Xuehui; Jiang, Hong; Yang, Fang; Yu, Chengzhi; Liu, Jianshe
Abstract : HOA and HON were key fractions involved in increasing antiestrogenic activity and humic/fulvic acid in them could mask estrogenic activity. Abstract : The presence of estrogenic/antiestrogenic chemicals in textile dyeing wastewater has been well demonstrated according to previous studies. However, the characteristics of estrogenic/antiestrogenic activities during conventional biological treatment have been poorly investigated. In this study, the yeast two-hybrid assay (YES) was used to evaluate the agonistic and antagonistic estrogen activities during the anoxic/aerobic treatment of textile dyeing wastewater. The results indicated that the estrogenic activity of the textile dyeing wastewater was negligible throughout the anoxic/aerobic treatment, but the antiestrogenic activity increased obviously after the aerobic treatment. By fractionating the dissolved organic matter (DOM) in wastewater into different fractions, it was found that hydrophobic acids (HOA) and hydrophobic neutrals (HON) were the key fractions involved in increasing antiestrogenic activity of the wastewater during anoxic/aerobic treatment. Furthermore, the fluorescence spectroscopy analysis on wastewater samples and their fractions of soluble organic compounds suggested that HOA and HON fractions contained more humic/fulvic acid in aerobic effluent than that in anoxic effluent, which could mask estrogenic activity in aerobic effluent.